Association between overweight, obesity, and quality of life of patients receiving an anticancer treatment for prostate cancer: a systematic literature review - Léonard Depotte; Maryline Caroux; Joseph Gligorov; Florence Canouï-Poitrine; Yazid Belkacemi; Alexandre De La Taille; Christophe Tournigand; Emmanuelle Kempf (Health and Quality of Life Outcomes, 2023)
Abstract Background Prostate cancer (PCa) and obesity are two ever-increasing public health issues that can independently impair the quality of life (QOL) of affected patients. Our objective was to evaluate the impact of overweight and obesity on the QOL of patients with PCa receiving an anticancer treatment. Methods We performed a systematic review of the literature using PubMed, Embase, Cochrane Library and Web of Science databases according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The search equation targeted studies that included PCa patients who had a body mass index (BMI) greater than 25 kg/m2, who were receiving anticancer therapy, and whose QOL was analyzed according to validated or non-validated scores. Results Of 759 identified articles, we selected 20 studies published between 2000 and 2019 of 12,529 patients treated for PCa, including 5549 overweight or obese patients. QOL assessment was performed using nine validated scales and two non-validated questionnaires. Of seven studies on radiotherapy, six found obesity to have a negative impact on patients' QOL (especially urinary, sexual, and bowel-related QOL). Thirteen studies assessed the QOL of patients who underwent radical prostatectomy, with a BMI > 25 kg/m2 having no observed impact. In obese patients under 65 years of age and without comorbidities, nerve-sparing surgery appeared to limit the deterioration of QOL. Four studies on brachytherapy found discordant results. One study showed greater QOL impairment in obese patients receiving first-generation hormone therapy than in those with normal or decreased BMI. No study evaluated the QOL of overweight or obese patients receiving other types of systemic treatment. Conclusion Based on the published data, the level of evidence for an association between QOL and overweight or obesity in patients treated for PCa is not high. Prospective cohort studies including this type of patient population are warranted to answer this topical public health issue.